The Status Of Iodine Nutrition Among Pupils Aged 6-12 Years of Hillcrest Schools In Cape Coast In The Central Region Of Ghana – Analysis of Urine Samples - Bartels Benjamin; Gadzekpo Victor Patrick Yao, (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2023)
The incidence of iodine deficiency among school-age children is a global concern due to its negative effect on their brain development and academic performance. Such, necessitated this study among the pupils of Hillcrest Schools aged 6-12 years during the 2016/17 academic year in the Cape Coast Metropolis. One hundred and ninety-six (196) urine samples were collected for their iodine concentrations using the Sandell-Kolthoff reaction. The median urinary iodine concentration obtained for the population was 102.14 µg/L at 95% CI. The lower (Q1) and the upper (Q2) quartiles were respectively 81.33 and 138.51. Forty- eight percent (48%) of the samples had urinary iodine concentration below 100 µg/L, and none below 50 µg/L. In addition, one percent was above 300 µg/L. The median value suggests that the pupils had adequate iodine intake and optimal iodine nutrition. This notwithstanding, the inter quartile range (IQR) suggests a polarity of mild iodine deficiency and adequate iodine intake. The study therefore shows that the universal salt iodization programme and the schools’ initiative on consumption of iodized salt are having the required impact.